2012
DOI: 10.1007/s12640-012-9365-0
|View full text |Cite
|
Sign up to set email alerts
|

Organochalcogens Inhibit Mitochondrial Complexes I and II in Rat Brain: Possible Implications for Neurotoxicity

Abstract: Organochalcogens, such as organoselenium and organotellurium compounds, can be neurotoxic under experimental conditions. Since mitochondrial dysfunction plays a pivotal role in neurological disorders, the present study was designed to test the hypothesis that rat brain mitochondrial complexes (I, II, I–III; II–III and IV) are molecular targets of organochalcogens. The results show that organochalchogens caused a statistically significant inhibition in mitochondrial complex I activity, which was prevented by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In an extension of this study, using renal and hepatic mitochondria, ebselen and diphenyl diselenide inhibited the activity of complex I and II, without changing the complex III and IV. These effects were reversed by GSH and then related to the oxidation of critical thiol groups from mitochondrial complexes I and II (Puntel et al 2013 ).…”
Section: Toxicity Of Organoselenium Compoundsmentioning
confidence: 99%
“…In an extension of this study, using renal and hepatic mitochondria, ebselen and diphenyl diselenide inhibited the activity of complex I and II, without changing the complex III and IV. These effects were reversed by GSH and then related to the oxidation of critical thiol groups from mitochondrial complexes I and II (Puntel et al 2013 ).…”
Section: Toxicity Of Organoselenium Compoundsmentioning
confidence: 99%
“…In this context, other studies showed that E. coli exposed to tellurium compounds exhibited a decrease in ATP levels, an increase in ROS generation, carbonylation of proteins, and a decrease in cellular reduced-thiol content [14,15,17,38,39]. The oxidation of thiols is associated with cell toxicity and death [17,23,24].…”
Section: Discussionmentioning
confidence: 98%
“…A telluroacetylene compound, 2-phenylethynylbutyltellurium (PEBT), at a low concentration has shown pharmacological effects in animal models of neurotoxicity and memory [20][21][22]. In contrast, several studies have established the toxicity of organotellurium compounds, including PEBT, which is associated with the oxidation of thiol groups in bioactive molecules, inhibiting sulfhydryl enzymes (δ-aminolevulinate dehydratase and Na + K + ATPase), or even decreasing the glutathione (GSH) concentration [20,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of complex I was determined spectrophotometrically at 30 ºC using mitochondria prepared as above and suspended in 100 mM phosphate buffer (pH 7.4) as previously described (Navarro et al 2002(Navarro et al , 2004. The reaction was initiated by addition D r a f t of NADH at a final concentration of 100 µM, and the enzymatic activity was determined by following the decrease in absorbance at 340 nm (Puntel et al 2013).…”
Section: Mitochondrial Complex Activity Assaymentioning
confidence: 99%